PERAN PEMASARAN DIGITAL DALAM MENGEMBANGKAN BISNIS SYARIAH - Dihan Rhofhatunnnisa; Dewi Sartika; Kristina Selvi; Ahmad Rafi Anhar (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
Current developments and business complexity encourage companies to manage customer relationships and increase competitiveness through digital marketing in line with sharia business development. This research explores the role of digital marketing in sharia business in the digital era, with the aim of understanding marketing dynamics, focusing on the implementation of sharia business, and its impact on consumer trust. The research method uses a descriptive qualitative approach with literature study. The research results show that platforms such as YouTube, Facebook, and Instagram have a big impact on increasing visibility and reaching a wide audience. The implementationof sharia business brings the values of justice, transparency and integrity in marketing, creating a business environment that complies with sharia. The research conclusion confirms that digital marketing is effective for sharia business development if implemented according to Islamic principles, with success depending on the harmony of digital innovation, sharia business values, and compliance with Islamic ethics, which builds consumer trust and supports business growth in the digital era.